Essential oils from Hyptis marrubioides, Aloysia gratissima and Cordia verbenacea reduce the progress of Asian soybean rust - André Costa da Silva; Paulo Estevão de Souza; Douglas Carvalho Amaral; Walmes Marques Zeviani; José Eduardo Brasil Pereira Pinto (Acta Scientiarum. Agronomy, 2014)
The aim of this study was to evaluate the potential of essential oils derived from Hyptis marrubioides, Aloysia gratissima and Cordia verbenacea for controlling Asian soybean rust. The inhibitory activities of the essential oils (applied in a concentration range of 0.05 - 2%) on the germination of Phakopsora pachyrhizi urediniospores were investigated using in vitro assays. The curative and eradicating properties of the oils (applied in a concentration range of 0.05 - 0.5%) were studied under greenhouse conditions using the P. pachyrhizi-susceptible soybean cultivar MG/BR 46 (Conquista). Scanning electron microscopy was employed to investigate the effects of the essential oils on the morphology of the P. pachyrhizi urediniospores. The treatment with the essential oils at all concentrations tested led to the total inhibition of spore germination in vitro. The curative application of the essential oils reduced the disease severity, expressed as the area under the disease-progress curves, by 33 to 41%, whereas the commercial fungicide (pyraclostrobin + epoxyconazole) employed as a positive control reduced the severity by 61%. The treatment of infected plants with the essential oils resulted in morphological alterations in the fungal structures that were similar to those produced by the commercial fungicide, namely, a shrivelling of the urediniospores, appressoria, germ tubes and paraphyses.